2018
DOI: 10.1002/gps.4968
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hearing loss in older adults and depression over 12 years: Findings from the Three‐City prospective cohort study

Abstract: Both mild and severe thresholds of HL are associated with depression symptoms over time, but not with incident diagnosis of major depression. Improved and ongoing detection of subthreshold depression amongst older adults with HL may improve quality of life for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 40 publications
3
46
0
4
Order By: Relevance
“…Mixed HL thresholds have also been used in the literature. While depression symptoms were observed both in mild and in severe self-reported HL,14 several large-scale studies have indicated that severity of HL is associated with increased depression risk,27,28 indicating a graded relationship between HL and depression. Accordingly, strengths of relationships and risk estimates of comorbid HL and depression can vary based on HL assessment methods.…”
Section: Hl and Depressionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mixed HL thresholds have also been used in the literature. While depression symptoms were observed both in mild and in severe self-reported HL,14 several large-scale studies have indicated that severity of HL is associated with increased depression risk,27,28 indicating a graded relationship between HL and depression. Accordingly, strengths of relationships and risk estimates of comorbid HL and depression can vary based on HL assessment methods.…”
Section: Hl and Depressionmentioning
confidence: 98%
“…Within the older adult population with HL, prevalence estimates of comorbid unipolar depression remain varied, but suggest that up to 1 in 5 older adults with HL report a clinically relevant level of depression symptoms that would necessitate treatment,13 and a further 22% experience the onset of incident depression symptoms over time 14. An emerging body of research further indicates that HL increases the risk of experiencing depression.…”
Section: Hl and Depressionmentioning
confidence: 99%
“…14 Interestingly, mainly minor depressive symptoms and not severe depression seem to be highly associated with hearing impairment in the long-term follow-up as reported by Cosh in a study on 8340 adults. 3 This might be even more pronounced in adults aged <65 years. 15 , 16 Besides the negative impact of age on sensory abilities, aging is associated also with an enhanced cognitive decline starting already from the second decade of life.…”
Section: Introductionmentioning
confidence: 98%
“…Several longitudinal studies have demonstrated that hearing loss increases the risk of incident all-cause dementia, with a relative risk that augments linearly with the severity of hearing loss (Lin et al, 2011;Gallacher et al, 2012;Deal et al, 2016). In addition to its association with cognitive decline, hearing loss has been related with increased risk of depressive symptoms (Brewster et al, 2018;Cosh et al, 2018). Therefore, the comorbidity of disorders that are risk factors for dementia or functional disability -such as presbycusis and NPS -is very common in the elderly, as many of them are related with the aging process (Livingston et al, 2017).…”
mentioning
confidence: 99%